Flexible Endoscopy With Non-invasive Ventilation Enables Clinicians to Assess and Manage Infants With Severe Bronchopulmonary Dysplasia - Soong, Wen-Jue; Tsao, Pei-Chen; Yang, Chia-Feng; Lee, Yu-Sheng; Lin, Chien-Heng; Chen, Chieh-Ho (Frontiers in Pediatrics, 2022)
Objectives The objectives of the study were to determine the efficacy of flexible endoscopy (FE) to assess the approachable aeroesophageal tract (AET) and subsequent changes in clinical management in infants with severe bronchopulmonary dysplasia (sBPD). Methods This retrospective study investigated sBPD infants who received FE measurement from 2011 to 2020. FE was supported with non-invasive ventilation (FE-NIV) of pharyngeal oxygen with nose closure and abdominal compression without any mask or laryngeal mask airway. Data on AET lesions, changes in subsequent management, and FE therapeutic interventions were collected and analyzed. Results Forty-two infants were enrolled in the study. Two thin scopes (1.8- and 2.6-mm outer diameter) were used. FE analysis revealed 129 AET lesions in 38 (90.5%) infants. Twenty-eight infants (66.7%) had more than one lesion. Thirty-five (83.3%) infants had 111 airway lesions where bronchial granulations (28, 25.2%), tracheomalacia (18, 16.2%), and bronchomalacia (15, 13.5%) were the main complications. Eighteen esophageal lesions were found in 15 (35.7%) infants. No significant FE-NIV complications were observed. The FE findings resulted in changes in management in all 38 infants. Thirty-six (85.7%) infants underwent altered respiratory care with pressure titrations (29, 45.3%), shortened suction depth (17, 26.6%), immediate extubation (8, 12.5%), changed insertion depth of endotracheal tube (7, 10.9%) and tracheostomy tube (3, 4.7%). Twenty-one (50%) infants had 50 pharmacotherapy changes, including added steroids, anti-reflux medicine, antibiotics, and stopped antibiotics. Eighteen (42.8%) infants received 37 therapeutic FE-NIV procedures, including 14 balloon dilatations, 13 laser-plasty, and 10 stent implantations. Seven (16.7%) infants underwent surgeries for four tracheostomies and three fundoplications. Conclusion Flexible endoscopy with this non-invasive ventilation could be a safe and valuable technique for direct and dynamic visual measurement of AET, which is essential for subsequent medical decision making and management in infants with sBPD.